A tool supporting role and task models in usage- centered design approach / Rafidah Pakir Mohamad - Rafidah , Pakir Mohamad (2003)
Usage-centered design approach highlights model-driven design, which helps the user interface designer to design user interface through visual models. These visual models makes the communication and understanding between user, designer and among development team easier. Based on these understanding the user interface designer will design a more effective user interface. Focus of this research is to develop a tool, which automate the role and task models used in analysis phase of model-driven design. Firstly, a literature review of system development design approaches was identified. These system development design approaches are system-centered, user-centered and usage-centered. Usage-centered design engaged model-driven design as one of the key element. The investigation is focused on the techniques of role and task models in the analysis phase of model-driven design. The identified techniques that support role model are card sorting and use-case diagram. And, task models support by task analysis technique. Card sorting and task analysis techniques were investigated in detail. Existing tools that support card sorting and task analysis technique are identified and studied to obtain an idea how the tools were created, their advantages and disadvantages. A prototype tool named as CaSTA is built that automates card sorting and task analysis techniques. To evaluate CaSTA, a pilot study was carried out by developing a mailing system for Human Computer Interaction Lab. The results reported are satisfactory.